The opaqueness of rules - Hass, B (Oxford University Press, 2020)
This article takes up the question of whether legal rules are reasons for action. They are commonly regarded in this way, yet are legal rules reasons for action themselves (the reflexivity thesis) or are they instead merely statements of other reasons that we may already have (the paraphrastic thesis)? I argue for a version of the paraphrastic thesis. In doing so, considerable attention is given to the neglected but important puzzle of the opaqueness of rules, which arises out of what some regard as the gap between the evaluative grounds of legal rules and what makes them into reasons for action. After examining an important articulation of the puzzle in the work of Joseph Raz, I argue that the reflexivity thesis is (i) undermined by certain features of rule making and (ii) defeated by the principle of presumptive sufficiency. The result is that it is possible for legal rules to be paraphrastic statements of reasons but, conversely, impossible for them to be reasons in themselves.